2016
DOI: 10.1002/2016gl069314
|View full text |Cite
|
Sign up to set email alerts
|

Using timing of ice retreat to predict timing of fall freeze‐up in the Arctic

Abstract: Reliable forecasts of the timing of sea ice advance are needed in order to reduce risks associated with operating in the Arctic as well as planning of human and environmental emergencies. This study investigates the use of a simple statistical model relating the timing of ice retreat to the timing of ice advance, taking advantage of the inherent predictive power supplied by the seasonal ice‐albedo feedback and ocean heat uptake. Results show that using the last retreat date to predict the first advance date is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 26 publications
6
74
3
Order By: Relevance
“…Under such maritime activities in the Arctic Ocean, forecasts of the local sea ice distribution rather than the total sea ice extent become of greater interest for marine users. Recent studies have reported the forecast skills of the retreat and advance dates of the sea ice distribution based on statistical methods (e.g., Stroeve et al, 2016;Wang et al, 2016) as well as a dynamical forecast system Bushuk et al, 2017). In the present study, our hindcasts could not reproduce precise seaice edges from summer to fall.…”
Section: Discussioncontrasting
confidence: 72%
“…Under such maritime activities in the Arctic Ocean, forecasts of the local sea ice distribution rather than the total sea ice extent become of greater interest for marine users. Recent studies have reported the forecast skills of the retreat and advance dates of the sea ice distribution based on statistical methods (e.g., Stroeve et al, 2016;Wang et al, 2016) as well as a dynamical forecast system Bushuk et al, 2017). In the present study, our hindcasts could not reproduce precise seaice edges from summer to fall.…”
Section: Discussioncontrasting
confidence: 72%
“…The link between MO and the timing of ice retreat has already been established, with correlations between the detrended melt onset and detrended ice retreat dates greater than 0.4 (see Fig. S10; Stroeve et al, 2016).…”
Section: Changes In the Melt Seasonmentioning
confidence: 82%
“…First the trend, up to 60% of which is a likely consequence of greenhouse gas forcing and increased Arctic amplification, with the remainder being due to internal variability (Kay et al 2011;Stroeve et al 2012). Second, there is the interannual variability of autumn sea ice coverage, which can be influenced by initial ice conditions, summer weather conditions, and storms in the Arctic, which can affect the amount of solar radiation absorbed by the ocean, and poleward atmospheric moisture and heat fluxes and oceanic heat fluxes Park et al 2015;Stroeve et al 2016). It is possible that some of these factors influencing sea ice interannual variability, such as shifts in the Gulf Stream, may themselves be effective predictors of the NAO, and the sea ice in fact modulates such a signal (e.g., Sato et al 2014).…”
Section: Discussionmentioning
confidence: 99%